Práticas do total quality management (TQM) na indústria farmacêutica - Torres, Vitória da Silva (2024)
The current scenario presents the pharmaceutical industry with a dynamic and competitive environment, with ever greater challenges in the quest for operational excellence and product quality assurance. Total Quality Management (TQM) has emerged as an essential approach to meeting these challenges, providing significant improvements in production processes, reducing failures and increasing consumer satisfaction. The aim of this study is to analyze research on Total Quality Management practices in the pharmaceutical industry. To this end, a Systematic Review was carried out to identify articles that would contribute to the research. The final portfolio of this study comprised a sample of 33 articles, selected from 229 publications, as well as 4 books and 4 regulatory standards. The review included publications from databases such as Web of Science, Scopus, SciELO, Google Scholar and CAPES. Analysis of the articles enabled us to identify how TQM contributes to generating quality in the pharmaceutical industry, highlighting the main practices and methodologies employed. The results showed that the implementation of TQM, often complemented by methods such as Analytic Hierarchy Process (AHP), Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), Total Productive Maintenanc (TPM) e Supply Chain Management (SCM), is fundamental to ensuring compliance with strict regulations and competitiveness in the global market. TQM practices allow for more strategic and results-oriented management, promoting continuous improvement, innovation in production processes and product safety. Overall, TQM has established itself as a robust and versatile strategy, indispensable for quality management and competitiveness in the pharmaceutical industry. This study suggests that the adoption of TQM, together with other methodologies, should be seen as an essential investment for any pharmaceutical company that aspires to stand out on the global stage, contributing to the safety, efficacy and quality of medicines.